An Evaluative Study on the Accreditation of Academic Programmes and Quality Assurance in Public Universities in Nigeria - Comfort Olufunke Akomolafe; Veronica Olubunmi Adesua (European Scientific Journal, ESJ, 2019)
The licensing of Universities is not just a yardstick or criteria to set up and operate a university system in Nigeria. Certain quality indices set standards, operational guides and discipline needs to be ensured to satisfy the minimum academic standards. The accreditation of such university needs to be put into consideration and embarked upon to ensured quality assurance of the academic programmes. This paper examined academic programme and quality assurance in public universities in southwest Nigeria. Descriptive research design was adopted. To carry out the study a research instrument titled “Questionnaire on Academic Programme and Quality Assurance in Nigerian Public Universities: (QAPQANPU)” was administered to elicit information from respondents. The population of the study comprises all academic staff in public Universities in Southwest, Nigeria. The sample of the study comprises three hundred and fifty-one (351) respondents. Purposive sampling technique was used to select four public universities in Southwest, Nigeria. Three research questions were formulated, it was revealed that accreditation had positive impact on quality assurance, the level of participation of academic staff in accreditation exercise was low and the level of accreditation of academic programme was very high. Two hypotheses were tested, hypothesis one was tested using t-test and hypothesis two was tested using Analysis of variance (ANOVA). The hypotheses were tested at 0.05 level of significance. The two hypotheses were not rejected. The findings revealed that there was no significant difference between male and female lecturers’ perception of the impact of accreditation on university quality assurance, also there was no significant difference between the perceptions of the impact of the accreditation by academic staff based on their status. Based on the findings of this study it was recommended that academic programmes in Nigeria universities should be accredited from time to time through the Nigeria University Commission (NUC) to ensure quality assurance and satisfy the minimum academic standards (MAS). Moreover, more academic staff should participate in accreditation exercise, once they have the experience and are qualified to encourage wider participation in various discipline/fields of study. Also government who is the proprietor of these public universities should provide adequate funds to improve the academic standards in Nigerian Universities.